The Ineffectiveness of Criminal Sanctions in Corruption Cases of COVID-19 Handling Funds in Indonesia - Trini Handayani; Nahknur Wudhi Ainnaiha (Sekolah Tinggi Hukum Bandung, 2025)
This research examines the effectiveness of criminal consequences for corruption offences in COVID-19 handling funds in Indonesia. The research analyses laws and regulations related to disaster management and social assistance funds. The research reveals legal uncertainty due to normative tensions in the legal framework, such as the absence of the death penalty in Government Regulation in Lieu of Law (Perpu) No. 1 of 2020. This research is a descriptive, employing a normative legal research type that utilizes secondary data comprising primary, secondary, and tertiary legal sources. The approach adopted is a legislative approach, with data collection techniques conducted through a literature study. Subsequently, the collected data is analyzed qualitatively. The case study of former Minister of Social Affairs, Juliari Batubara, highlights shortcomings in law enforcement. The study suggests a constitutional review of laws for non-natural disasters to ensure efforts to combat corruption. Furthermore, it recommends the implementation of more robust regulatory mechanisms and stringent punitive measures to strengthen institutional integrity and preserve public trust in judicial processes.